WEAKLY CONTRACTIVE MAPPING IN PARTIAL METRIC SPACE - Sagita Charolina Sihombing (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
Contractive mapping is one kind of mapping that guarantees a fixed point in a metric space  Many experts has developed this kind of mapping to show the existence of a fixed point such as Kannan mapping and Chatterjea Contractive mapping. In this study, we will show the weakly contractive mapping to show the existence of fixed point in the partial metric space